2015
DOI: 10.3390/ma8030899
|View full text |Cite
|
Sign up to set email alerts
|

Composite Behavior of a Novel Insulated Concrete Sandwich Wall Panel Reinforced with GFRP Shear Grids: Effects of Insulation Types

Abstract: A full-scale experimental program was used in this study to investigate the structural behavior of novel insulated concrete sandwich wall panels (SWPs) reinforced with grid-type glass-fiber-reinforced polymer (GFRP) shear connectors. Two kinds of insulation-expanded polystyrene (EPS) and extruded polystyrene (XPS) with 100 mm thickness were incased between the two concrete wythes to meet the increasing demand for the insulation performance of building envelope. One to four GFRP shear grids were used to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…During the initial stage of the test, the CTR and HFC specimens remained plane and failed due to the initiation of shear cracking so that they followed the assumption made for the theoretical framework. Meanwhile, the JFC specimens did not follow this as the collapsed mechanism initiated was a debonding mechanism, such as reported in Reference [26], so that the cross section did not remain plane when bending took place. In short, it can be inferred that debonding mechanism is also an important aspect when further developing this new hybrid panel in the future.…”
Section: Comparison Of Load-deflection Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…During the initial stage of the test, the CTR and HFC specimens remained plane and failed due to the initiation of shear cracking so that they followed the assumption made for the theoretical framework. Meanwhile, the JFC specimens did not follow this as the collapsed mechanism initiated was a debonding mechanism, such as reported in Reference [26], so that the cross section did not remain plane when bending took place. In short, it can be inferred that debonding mechanism is also an important aspect when further developing this new hybrid panel in the future.…”
Section: Comparison Of Load-deflection Behaviourmentioning
confidence: 99%
“…The early separation of the intermediate layer and the EPS core was resulted from the low bond strength of the two adjacent materials. Such failure mechanism was also reported previously for the sandwich structure with EPS and XPS foam core [26]. Furthermore, the theoretical concept of sandwich panel was developed based on the assumption that the cross-sections are plane and perpendicular to the longitudinal axis of the unloaded beam [2,46].…”
Section: Comparison Of Load-deflection Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…The early delamination process at the interface of the intermediate layers and the core may have resulted from the low bond strength of the two adjacent materials. Kim and You (2015) and Fajrin et al (2016) reported a similar failure mechanism for sandwich structures with EPS and XPS foam core.…”
Section: Comparison Of Load-deflection and Load-strain Behaviormentioning
confidence: 86%
“…This work characterizes the effect of ceramic powder on the far-infrared emissivity of polymer composites. Three different types of cFIR composite films were fabricated using a sandwich structure process (shown in Figure 1) that can enhance breakdown strength [23]. The cFIR films also show significant potential as packaging materials, as they can improve the shelf life of fruits owing to their biological effects.…”
Section: Introductionmentioning
confidence: 99%